Aberrant Dependence of Default Mode/Central Executive Network Interactions on Anterior Insular Salience Network Activity in Schizophrenia - Manoliu, Andrei (Oxford University Press, 2014)
In schizophrenia, consistent structural and functional changes have been demonstrated for the insula including aberrant salience processing, which is critical for psychosis. Interactions within and across default mode and central executive network (DMN, CEN) are impaired in schizophrenia. The question arises whether these 2 types of changes are related. Recently, the anterior insula has been demonstrated to control DMN/CEN interactions. We hypothesized that aberrant insula and DMN/CEN activity in schizophrenia is associated with an impaired dependence of DMN/CEN interactions on anterior insular salience network (SN) activity. Eighteen patients with schizophrenia during psychosis and 20 healthy controls were studied by resting-state-fMRI and psychometric examination. High-model-order independent component analysis of fMRI data revealed spatiotemporal patterns of synchronized ongoing blood-oxygenation-level-dependent (BOLD) activity including SN, DMN, and CEN. Scores of functional and time-lagged connectivity across networks’ time courses were calculated. Connectivity scores and spatial network maps were compared between groups and related with patients’ hallucination and delusion severity. Spatial BOLD-synchronicity was altered in patients’ SN, DMN, and CEN, including decreased activity in the right anterior insula (rAI). Patients’ functional connectivity between DMN and CEN was increased and related with hallucinations severity. Importantly, patients’ time-lagged connectivity between SN and DMN/CEN was reduced, and decreased rAI activity of the SN was associated with both hallucinations and increased functional connectivity between DMN and CEN. Data provide evidence for an aberrant dependence of DMN/CEN interactions on anterior insular SN activity, linking impaired insula, DMN, CEN activity, and psychosis in schizophrenia.